Measuring school social climate in Latin America: the need for multidimensional and multi-informant tests – A systematic review - Bravo-Sanzana, Mónica V.; Varela, Jorge; Terán-Mendoza, Oscar; Rodriguez-Rivas, Matias E. (Frontiers in Psychology, 2023)
Introduction School social climate is central to understanding learning experiences in education environments. Previous studies describe various conceptual and operational definitions around the construct; however, there are no records of reviews focused on Latin America. Aim This study sought to analyze the available evidence and the quality of school social climate measures in Latin America through a systematic review of the literature based on the PRISMA methodology and the COSMIN checklist to assess the psychometric properties of the instruments. Methodology The Web of Science, Scopus, Psycinfo, and SciELO databases were consulted. A total of 582 records was identified, of which 27 fulfilled the inclusion criteria and methodological quality to be included in the systematization. Results The results show that the country with the greatest scientific production on the topic is Chile, the measures are centered mainly on the students’ perspective and the most used instrument is the CECSCE. In addition, a common aspect to all the records is that they were not sufficient to capture the complexity of school social climate. Conclusion Multidimensional and multi-informant measures are needed to adequately assess the construct.